Community-led Recovery from the Opioid Crisis through Culturally-based Programs and Community-based Data Governance - Maar, Marion; Ominika, Tim; Manitowabi, Darrel (The International Indigenous Policy Journal)

(untitled) (Scholarship@Western (Western University), 2022)
The opioid crisis is disproportionately impacting Indigenous communities in Canada. There is a need to evaluate practical approaches to recovery that include community-based opioid agonist treatment (OAT) and integration of cultural treatment models. Naandwe Miikan, translated as The Healing Path, is an OAT program that blends clinical and Indigenous healing concepts and providers in a community-based setting. Aside from OAT pharmaceutical treatment, clients work with Indigenous counsellors that integrate culture with treatment, such as land-based activities, that reconnect the community to Indigenous teachings and harvesting. In this paper, we present a case study showcasing community advocacy in creating innovative funding models and engaging with clinicians to provide a shared care OAT model with traditional Indigenous counselling, cultural programs, and data sovereignty. Policy needs are identified.